Between Home and Home: Crossings and Coastlines in the Poetry of Boey Kim Cheng - Leow, Joanne (SARE: Southeast Asian Review of English, 2017)
In writing about the Black Atlantic, Paul Gilroy contrasts "the sea's liquid contamination" which "involves both mixture and movement" with the land "where we find that special soil in which we are told national culture takes root" (2). In my reading of Singapore-born Australia-based Boey Kim Cheng's poetry, I want to suggest an alternative way of looking at Singaporean writing in English which privileges precisely the kind of "mixture and movement" that Gilroy describes. Examining a selection of Boey's poems across his career, I will consider the repeated motifs of journeys and crossings which are frequently associated with the sea and coastline.